A classical [V10O28]6− anion templated high-nuclearity silver thiolate cluster. Issue 66 (28th July 2022) - Li, Li; Zhu, Yanjie; Han, Baoliang; Wang, Qiongyi; Zheng, Luming; Feng, Lei; Sun, Di; Wang, Zhi
Abstract : The largest known polyoxovanadate-templated silver nanocluster (Ag50 ) was synthesized, and the box-like V10 O28 @Ag50 structure displays the geometric inheritance from the internal decavanadate to the silver skeleton. Abstract : Polyoxovanadates (POVs) as templates are still scarcely observed in silver clusters. Herein, the largest known POV-based silver cluster (Ag50 ) was synthesized, which is a core–shell conformation composed of the in situ generated classical [V10 O28 ] 6− core and Ag50 shell, constrained by the S- and O-donor ligands with a specific distribution. Such V10 O28 @Ag50 structure displays geometric inheritance from the D 2h symmetric decavanadate to the silver skeleton. The solution behavior, solid-state stability and photoelectric properties are discussed in detail. This work provides enlightenment for the further construction of POV-templated high-nuclearity silver clusters.